Legal Recognition Of Online Arbitration In Indonesia Related With China International Economic And Trade Arbitration Commission Online Arbitration Rules (Cietac Oar) - Dewanto, Jagad Putra; Amalia, Prita; Budhijanto, Danrivanto (Universitas Muhammadiyah Sumatera Utara, 2024)
The development of electronic commerce has opened up the possibility of disputes among cross-border traders. Online Dispute Resolution (ODR) is one emerging form of dispute resolution adopted by China through the China International Economic and Trade Arbitration Commission (CIETAC). While Indonesia has regulations such as Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution and BANI Rules 2022 governing the electronic correspondence process of dispute resolution, ODR is not explicitly addressed. This research examines the legal recognition of ODR in Indonesia and explores the urgency of establishing ODR institutions with reference to CIETAC. The research findings indicate that Indonesia has not explicitly recognized ODR, signifying the urgent need to establish ODR platforms and revise arbitration regulations and dispute resolution in Indonesia. China's experience in recognizing ODR through the establishment of platforms and regulatory updates in its arbitration regime can serve as guidance for Indonesia in the future